A Ka‐band power divider/combiner using two side‐inserted magnetic coupling semicircular ring probes. Issue 9 (25th June 2020) - Li, Lei; Lei, Guozhong; Zhu, Shitao; Zhan, Ting
Abstract: A Ka‐band power divider/combiner with dual magnetic coupling semicircular ring probes is proposed in this paper. Firstly, a broadband microstrip‐to‐waveguide transition with semicircular ring probe is designed based on the side‐inserted structure of magnetic field excitation in a rectangular waveguide. The insertion loss of the proposed transition is less than 0.7 dB in Ka‐band assisted by the dual symmetrical broadband probes and rectangular waveguide. Then, the divider/combiner is proposed using the new transition with magnetic coupling from narrow wall into the rectangular waveguide. The bandwidth of the divider/combiner is more than 9 GHz (from 27 to 36.7 GHz), and the insertion loss of the single divider/combiner is less than 3.3 dB. Finally, the performance of the proposed divider/combiner is validated through simulations and measurements. The proposed design has potential applications in microstrip circuits.